Black zirconia composite sintered body and manufacturing method thereof
By adding a specific proportion of components such as ZrO2, HfO2, stabilizer and Nb2O5 to the black zirconium nitrogen compound ceramic body, and containing elements or ions from the derivatizer, the problem of poor processing performance of the ceramic body in solid state is solved, and efficient processing and black appearance are achieved.
Patent Information
- Application Number
- JP2024217148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to provide a black zirconium nitrogen compound ceramic body with excellent processing properties in solid state, especially in maintaining a black appearance and improving processing properties.
By adding ZrO2 and HfO2, a stabilizer to the black zirconium nitrogen compound ceramic body to inhibit the phase transition of zirconium nitrogen, Nb2O5 and/or Ta2O5, and containing elements or ions from the derivatizer, the composition ratio and the content of the derivatizer are adjusted to improve the processing performance of the ceramic body.
A black zirconium nitrogen compound ceramic body with excellent processing performance in solid state is realized, which reduces processing time, reduces tool wear, improves the efficiency and economy of continuous processing, while maintaining the black appearance and high strength of the ceramic body.
Smart Images

Figure 2025038052000003 
Figure 2025038052000004 
Figure 2025038052000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a black zirconia composite sintered body and a method for producing the same, and more particularly to a black zirconia composite sintered body which is excellent in strength and in the sintered state in terms of workability, and a method for producing the same. [Background technology]
[0002] With the revolution in communication technology such as 5G, the radio waves used for communication are shifting to higher frequency bands. Metal is mainly used for the back plate of 5G compatible smartphones, but since metal is not suitable for transmitters and receivers of radio waves in the high frequency band, plastic, glass, and ceramics are used instead.
[0003] Among these, black ceramics have been used because of their high design value, such as giving a sense of luxury. There was also a need to use zirconia as a highly decorative ceramic. However, zirconia is a material that is difficult to process in the sintered state. Therefore, if zirconia sintered bodies were used as a partial material for smartphones, the processing costs would be high due to the difficulty of processing the sintered bodies.
[0004] Under these circumstances, since black is essential as the color of the housing of a smartphone, black-colored machinable ceramics have been developed by containing zirconia but not making it the main component (for example, Patent Document 1).
[0005] On the other hand, black zirconia sintered bodies have also been developed from the viewpoint of excellent designability, although they are significantly inferior in processability (for example, Patent Documents 2 and 3).
[0006] In addition, with regard to zirconia sintered bodies, although they are not black and are intended for the dental field, processable zirconia sintered bodies with improved processability have also been developed (for example, Patent Document 4). For example, Patent Document 4 describes a zirconia sintered body having 79.8 to 92 mol% ZrO 2 and 4.5 to 10.2 mol% Y2 O 3 and 3.5 to 7.5 mol% Nb 2 O 5 Or 5.5 to 10.0 mol% Ta 2 O 5 and a TiO having a mass ratio of more than 0 mass% to 2.5 mass% or less with respect to the zirconia composite powder. 2 A processable zirconia sintered body formed to contain a nanopowder and a method for producing the same are disclosed. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-354480 A [Patent Document 2] JP 2006-342036 A [Patent Document 3] JP 2017-77976 A [Patent Document 4] JP 2015-127294 A Summary of the Invention [Problem to be solved by the invention]
[0008] In Patent Document 1, zirconia is used as a black pigment by reduction firing. However, as the content of zirconia increases, the machinability decreases, so the blending ratio of zirconia is low.
[0009] Patent Document 2 proposes a zirconia sintered body with a deep black color. Patent Document 3 also proposes a black zirconia sintered body that addresses the problem of color tone change due to sintering when obtaining the zirconia sintered body.
[0010] However, both Patent Documents 2 and 3 fail to solve the problem of poor processability.
[0011] In addition, the zirconia sintered body disclosed in Patent Document 4 can be machined even in a sintered state. However, it is difficult to say that it has excellent processability, and the processing time for cutting out the processed body is long, so there is still room for improvement in processability. In addition, since it is not black but has excellent translucency, the color tone is completely different. Furthermore, although the zirconia sintered body disclosed in Patent Document 4 can be machined, the number of processed bodies obtained by continuous machining using one machining tool is small, and the machining tool wears quickly, so that the machining tool needs to be replaced more frequently, the tool replacement time increases, and productivity and economy decrease.
[0012] As described above, even in Patent Document 4, the zirconia sintered body is only said to be processable, and since there is a specific problem due to the sintered state of zirconia, that is, the zirconia sintered body is very difficult to process, it remains difficult to provide a zirconia sintered body that has excellent processability in the sintered body state, and a zirconia sintered body that has excellent processability in the sintered body state and is black in color has not been obtained.
[0013] An object of the present invention is to provide a zirconia composite sintered body which has excellent machinability in a sintered state and is black in color. [Means for solving the problem]
[0014] As a result of intensive research to solve the above problems, the present inventors have discovered ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 The inventors have found that the problem can be solved by further containing a capping element or ion in a black zirconia composite sintered body containing the above in a predetermined ratio, and have conducted further research based on this finding, thereby completing the present invention.
[0015] That is, the present invention includes the following inventions. [1] ZrO2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, A black zirconia composite sintered body, further comprising elements or ions derived from a capping agent. [2] The content of the element or ion derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The black zirconia composite sintered body according to [1], wherein the content of each of the above is more than 0 mol % and 5 mol % or less with respect to a total of 100 mol %. [3] A black zirconia composite sintered body according to [1] or [2], in which a sample 15 mm in diameter and 1.2 mm in thickness is used to measure the color of the sample against a white background using the L*a*b* color system, and the chroma C* calculated from a* and b* is 10 or less. [4] The black zirconia composite sintered body according to [1] or [2], wherein the colorimetric values measured on a sample having a diameter of 15 mm and a thickness of 1.2 mm against a white background using the L*a*b* color system are L*≦60, |a*|≦3, and |b*|≦3. [5] The black zirconia composite sintered body according to any one of [1] to [4], wherein the element or ion derived from the capping agent contains at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. [6] The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content of is Bmol%, The black zirconia composite sintered body according to any one of [1] to [5], wherein A / B is 0.9 or more and 3 or less. [7] The stabilizer is Y 2 O 3 and / or CeO 2 The black zirconia composite sintered body according to any one of [1] to [6], [8] Further comprising a zirconia reinforcement agent, the content of the zirconia reinforcement agent being ZrO 2 and HfO 2 and the stabilizer, and Nb 2 O 5 and Ta 2 O 5 The black zirconia composite sintered body according to any one of [1] to [7], wherein the content of the black zirconia composite sintered body is more than 0 mass % and 5.0 mass % or less with respect to 100 mass % of the total of the above. [9] The zirconia reinforcement agent is TiO 2 and / or Al 2 O 3 The black zirconia composite sintered body according to [8],
[10] The zirconia reinforcement agent is TiO 2 Contains TiO 2 The black zirconia composite sintered body according to [9], wherein the content of is 0.6 to 3.7 mass %.
[11] ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, producing a molded body using a raw material composition further containing a capping agent; and sintering the compact. The method for producing a black zirconia composite sintered body according to any one of [1] to
[10] .
[12] The step of sintering the molded body includes a step of reducing and firing the molded body.
[11] A method for producing a black zirconia composite sintered body according to the present invention.
[13] The capping agent contained in the raw material composition is a compound that can become a monovalent ion, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. The method for producing the black zirconia composite sintered body according to
[11] or
[12] .
[14] In the raw material composition, the stabilizer is ZrO 2 and HfO 2 The method for producing a black zirconia composite sintered body according to any one of
[11] to
[13] , further comprising a stabilizer that is not solid-dissolved in the zirconia composite sintered body. Effect of the Invention
[0016] According to the present invention, it is possible to provide a zirconia composite sintered body which has excellent machinability in a sintered state and is black in color. Furthermore, according to the present invention, a black zirconia composite sintered body can be provided which can be machined in a sintered body state, the machining time required for machining can be short, and wear on the machining tool can be suppressed. A large number of workpieces can be cut out by continuous machining using a single machining tool (hereinafter, also simply referred to as "continuous machining"), and which is therefore highly productive and economical. Furthermore, according to the present invention, a black zirconia composite sintered body having excellent strength and design properties can be provided. Furthermore, according to the present invention, the method for producing the black zirconia composite sintered body does not require pressure sintering. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic diagram showing an estimated structure of the black zirconia composite sintered body of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a presumed mechanism of action of elements or ions derived from the capping agent of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The black zirconia composite sintered body of the present invention is ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia (hereinafter also simply referred to as "stabilizer"), and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5and Ta 2 O 5 The total content of is 1 to 9 mol%, It further contains elements or ions derived from the capping agent.
[0019] The black zirconia composite sintered body of the present invention is ZrO 2 It means that the particles (powder) are in a completely sintered state (sintered state). In this specification, the upper and lower limits of the numerical ranges (contents of each component, ratios calculated from each component, values, and each physical property, etc.) can be appropriately combined. In this specification, machining includes cutting and grinding. The mechanical processing may be either wet processing or dry processing, and is not particularly limited.
[0020] In this specification, an element or ion derived from a capping agent (hereinafter also referred to as "capping element or ion") refers to an element or ion that caps the end of a bond of a zirconia-based composite oxide in a black zirconia composite sintered body composed of a zirconia-based composite oxide, thereby weakening the strength (hereinafter also referred to as "grain boundary strength") of a crystal interface (hereinafter also referred to as "grain boundary"). The capping agent is capable of capping a portion of the grain boundaries. The term "capping" refers to a state in which a target element or ion (capping element or ion) is bonded to a bond of the zirconia composite oxide in place of the metal element and is present at the grain boundary. It is presumed that the presence of capping elements or ions at grain boundaries in the form of +1-valent cations or -1-valent anions causes electrostatic repulsion between the capped cations or anions, weakening the grain boundary strength.
[0021] In this specification, the content of each component in the black zirconia composite sintered body can be calculated from the amount of the raw material charged. In addition, ZrO 2 , HfO 2 , stabilizer, Nb 2 O5 and Ta 2 O 5 The content of each component can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, or the like. The content (mol%) of elements or ions derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The external addition rate is based on a total of 100 mol%. Therefore, the content of the element or ion derived from the capping agent in the black zirconia composite sintered body can be calculated by converting the amount (mass) of the raw material added at the time of addition into mol%. The content (mass%) of the zirconia reinforcement agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The external addition rate is based on the total of 100 mass %. Therefore, the content of the zirconia reinforcing agent in the black zirconia composite sintered body can be calculated from the amount (mass) of the raw material added when it is added.
[0022] The reason why the black zirconia composite sintered body of the present invention has suitable strength and high machinability and can be machined in the sintered body state is not clear, but is presumed to be as follows. ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 In the black zirconia composite sintered body containing the above, it is presumed that the presence of capping elements or ions at the crystal grain boundaries reduces the grain boundary strength in the form of +1-valent cations or -1-valent anions, and acts in a direction that makes it easier for particles to peel off from each other, making it easier to cut, and improving machinability. The black zirconia composite sintered body of the present invention is ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transformation of zirconia, Nb 2 O 5 and / or Ta 2 O 5 and a capping element or ion-containing exfoliating component 2, and optionally ZrO 2 and HfO 2 and Nb 2 O 5 and / or Ta 2 O 5 and an adhesive component 3 containing a metal element (eg, Ti) derived from a zirconia reinforcing agent. ZrO 2 and HfO 2 and Nb 2 O 5 and / or Ta 2 O 5 That is, a part of each is present in both the zirconia particles 1 and the adhesive component 3 . Furthermore, in the zirconia composite sintered body of the present invention, grain boundaries 4 are also present where no exfoliation components 2 are present, and exfoliation components 2 containing capping elements or ions are present in an appropriate amount at the grain boundaries. It is therefore presumed that this makes it possible to appropriately reduce the grain boundary strength while minimizing the reduction in strength. A schematic diagram of an estimated structure of a zirconia composite sintered body according to an embodiment containing a zirconia reinforcement is shown in Fig. 1. Even when the adhesive component 3 of the zirconia composite sintered body containing a zirconia reinforcement is present, the effect of reducing the grain boundary strength obtained by the peeling component 2 is not suppressed, and the strength can be increased.
[0023] The capping element or ion becomes a +1-valent cation or -1-valent anion at the grain boundary of the black zirconia composite sintered body and bonds with the bonds of the zirconia composite oxide. This bond causes electrostatic repulsion between the cations or anions, which weakens the grain boundary strength while maintaining the strength properties of the particles constituting the black zirconia composite sintered body, and acts in the direction of improving machinability. For example, as shown in FIG. 2(a), a +1-valent cation may be bonded to the other bond of an oxygen atom bonded to a metal element (e.g., Zr, Hf, Y, Nb, or Ta) contained in the zirconia-based composite oxide in place of the metal element. + represents a +1 cation. As shown in FIG. 2(b), a −1-valent anion is bonded to a metal element (e.g., Zr, Hf, Y, Nb, or Ta) contained in the zirconia-based composite oxide. 2+ It is possible that the molecule may bind to Furthermore, as shown in FIG. 2(c), a form is considered in which a -1-valent anion is contained in the zirconia-based composite oxide and is bonded to a cation derived from a metal element (e.g., Zr, Hf, Y, Nb, or Ta) that is bonded to another metal element. In FIG. 2(b) and (c), X - represents a -1-valent anion. In FIG. 2, (a) to (c) show schematic diagrams of interactions between charged sites at grain boundaries and adsorption sites.
[0024] In addition, Nb 2 O 5 and / or Ta 2 O 5 In the black zirconia composite sintered body, Nb acts to coarsen the microstructure and reduce the hardness, so it is necessary to use a capping element or ion and Nb 2 O 5 and / or Ta 2 O 5 These elements work together to improve machinability. Therefore, the capping element or ion and Nb 2 O 5 and / or Ta 2 O 5 These functions work together to provide excellent machinability while maintaining suitable strength, and it is therefore expected that the machining time can be shortened, wear on the machining tools can be suppressed, and the number of processed bodies obtained by continuous machining using a single machining tool can be increased, thereby solving problems specific to the continuous machining of zirconia sintered bodies.
[0025] In the black zirconia composite sintered body of the present invention, the capping element or ion acts as an agent for imparting machinability as described above, and further does not significantly impair strength.
[0026] The content of the capping element or ion contained in the black zirconia composite sintered body of the present invention is preferably more than 0 mol% and 5 mol% or less, and from the viewpoint of excellent machinability and enabling a further increase in the number of workpieces that can be continuously machined with one machining tool, the content is more preferably 0.05 mol% or more and 3 mol% or less, even more preferably 0.06 mol% or more and 2.5 mol% or less, particularly preferably 0.07 mol% or more and 1.0 mol% or less, and most preferably 0.08 mol% or more and 0.34 mol% or less. Furthermore, when the capping element or ion contained in the black zirconia composite sintered body of the present invention is a Group 17 element or ion, in order to provide superior machinability and to increase the number of workpieces that can be continuously machined with one machining tool, the capping element or ion is more preferably 0.2 mol% or more and 5 mol% or less, even more preferably 0.3 mol% or more and 4 mol% or less, particularly preferably 0.4 mol% or more and 3.5 mol% or less, and most preferably 0.5 mol% or more and 3.0 mol% or less.
[0027] As described above, it is important that the capping element or ion is a +1-valent cation or a -1-valent anion and is present at the grain boundary in order to exhibit appropriate interaction between the charged sites at the grain boundary and the adsorption sites.
[0028] As the capping element or ion, preferred are elements or ions thereof belonging to the second to seventh periods of the periodic table and having a smaller first ionization energy than the group 18 elements of the same period, elements or ions thereof having high electron affinity, nitrate ions, hypochlorite ions, chlorite ions, chlorate ions, perchlorate ions, bromate ions, permanganate ions, metaborate ions, and cyanide ions. In one preferred embodiment, the black zirconia composite sintered body includes an element or an ion thereof derived from the capping agent, which belongs to Periods 2 to 7 of the periodic table and has a smaller first ionization energy than that of a Group 18 element in the same period, and / or an element or an ion thereof having a high electron affinity.
[0029] Preferred examples of elements belonging to the second to seventh periods of the periodic table and having a smaller first ionization energy than the group 18 elements in the same period include Cu, Ag, Li, Na, K, Rb, Cs, Fr, and the like, because they have an easier time obtaining a +1 valent cation and have excellent machinability.
[0030] As the element having a high electron affinity, the Group 17 elements are preferable because −1-valent anions are more easily obtained and machinability is superior. As the Group 17 elements, At, I, Br, Cl, and F are preferable.
[0031] The first ionization energy is the energy required to remove one electron from a neutral atom and ionize it. The first ionization energy can be the same as the first ionization energy described in "Schreiber-Atkins Inorganic Chemistry (Vol. 1), 4th Edition, Part I, Fundamentals, 1. Atomic Structure". The first ionization energy can be converted to "KJ / mol" units using the unit "eV" of first ionization energy described in "Schreiber-Atkins Inorganic Chemistry (Vol. 1), 4th Edition, Appendix 2" as 1 eV = 96.485 KJ / mol. The first ionization energy can also be determined by photoelectron yield spectroscopy (PYS). Electron affinity (EA) is the energy released when an electron is added to a neutral atom. Electron affinity can be measured by the difference in the energy gap from the ionization potential. The ionization potential is defined as the energy difference between the highest-energy occupied orbital of the compound's molecules and the vacuum level, and its value is measured using ultraviolet photoelectron spectroscopy. As the first ionization energy and electron affinity, data accumulated in the NIST Chemistry WebBook (https: / / webbook.nist.gov / chemistry / ) may be used (select Ionization Energy or Electron Affinity from Ion energetics properties). The first ionization energy and electron affinity are sufficient as long as they can compare the likelihood of an element becoming a +1-valent cation or a -1-valent anion with other comparison elements, and the measurement methods described above can be used as appropriate.
[0032] Specific examples of capping elements include Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. Of these, Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F are preferred in terms of further improving machinability. In a preferred embodiment, the element derived from the capping agent includes at least one element selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F, and the ion of the element is at least one +1-valent cation or -1-valent anion selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, I, Br, Cl, and F. In another preferred embodiment, the element or ion derived from the capping agent includes at least one element or ion thereof selected from the group consisting of Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F. The capping elements or ions may be used alone or in combination of two or more.
[0033] In the black zirconia composite sintered body of the present invention, ZrO 2 and HfO 2 The total content of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O5 , and Ta 2 O 5 In terms of superior strength, the content is preferably 79 mol% or more and 96 mol% or less, more preferably 80 mol% or more and 94 mol% or less, and even more preferably 81 mol% or more and 93 mol% or less. As described above, the black zirconia composite sintered body of the present invention is 2 O 5 and Ta 2 O 5 However, it acts to coarsen the microstructure and reduce hardness, and acts together with the capping elements or ions to provide excellent machinability, so ZrO 2 and HfO 2 Although the total content is high at 78 to 97.5 mol%, the sintered body has excellent machinability.
[0034] Examples of stabilizers capable of suppressing the phase transition of zirconia include calcium oxide (CaO), magnesium oxide (MgO), and yttrium oxide (Y 2 O 3 ), cerium oxide (CeO 2 ), Scandium oxide (Sc 2 O 3 ), lanthanum oxide (La 2 O 3 ), erbium oxide (Er 2 O 3 ), praseodymium oxide (Pr 2 O 3 ,Pr 6 O 11 ), samarium oxide (Sm 2 O 3 ), europium oxide (Eu 2 O 3 ) Thulium oxide (Tm 2 O 3 ), gallium oxide (Ga 2 O 3 ), indium oxide (In 2 O 3 ) and ytterbium oxide (Yb 2 O 3) and the like. In view of the superior effect of the present invention and particularly superior aesthetic appearance, Y 2 O 3 (yttria) and / or CeO 2 The stabilizer may be used alone or in combination of two or more kinds.
[0035] As mentioned above, the capping element or ion and Nb 2 O 5 and / or Ta 2 O 5 Since the above functions in combination and does not impair the effect of the stabilizer, the stabilizer is not particularly limited, and the effects of the present invention can be achieved.
[0036] In the black zirconia composite sintered body of the present invention, the content of the stabilizer capable of suppressing the phase transition of zirconia is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, the content is 1 to 12 mol%, and from the viewpoint of easily obtaining sufficient machinability, the content is preferably 2 mol% or more and 10 mol% or less, and from the viewpoint of obtaining superior strength, the content is more preferably 3 mol% or more and 8 mol% or less, and further preferably 3.5 mol% or more and 7.5 mol% or less. In a preferred embodiment, the stabilizer capable of suppressing the phase transformation of zirconia is Y 2 O 3 and / or CeO 2 Contains Y 2 O 3 , and CeO 2 The black zirconia composite sintered body may have a total content of from 2 mol % to 10 mol %. In another preferred embodiment, the stabilizer capable of suppressing the phase transformation of zirconia is Y 2 O 3 Contains Y 2 O 3The black zirconia composite sintered body has a content of from 2 mol % to 10 mol %. In any of the above embodiments, Y 2 O 3 , and CeO 2 The content of Y can be appropriately changed within the range described in this specification. For example, Y is preferably used in terms of superior strength. 2 O 3 , and CeO 2 The total content may be 2.5 mol % or more and 10 mol % or less, or may be 3 mol % or more and 9 mol % or less.
[0037] In the black zirconia composite sintered body of the present invention, Nb 2 O 5 and Ta 2 O 5 The total content of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In the total of 100 mol%, Nb is 1 to 9 mol%, preferably 1.5 mol% to 8.5 mol%, and more preferably 2.5 mol% to 8 mol%, and even more preferably 3 mol% to 7 mol% in view of its action together with the capping element or ion and its excellent machinability. 2 O 5 and Ta 2 O 5 If the total content is less than 1 mol%, it is difficult to obtain sufficient machinability. 2 O 5 and Ta 2 O 5 If the total content exceeds 9 mol %, the resulting black zirconia composite sintered body will have chips and will not exhibit sufficient physical properties.
[0038] Nb 2 O 5 and Ta 2 O 5As described above, the capping element or ion acts to coarsen the microstructure and reduce the hardness, and can impart excellent machinability by acting together with the capping element or ion. In addition, the capping element or ion acts in a manner similar to that of the other components (e.g., TiO 2 , Al 2 O 3 ) and the application of HIP to maximize the sintered density, making it easier to obtain black zirconia composite sintered bodies with superior design properties.
[0039] The above-mentioned ZrO 2 , HfO 2 , stabilizer, Nb 2 O 5 and Ta 2 O 5 The content of each component is ZrO 2 , HfO 2 , stabilizer, Nb 2 O 5 and Ta 2 O 5 is the percentage in the total of 100 mol%, ZrO 2 , HfO 2 , stabilizer, Nb 2 O 5 and Ta 2 O 5 The total of does not exceed 100 mol%. For example, the raw material composition is Nb 2 O 5 Including Ta 2 O 5 If it does not contain ZrO 2 , HfO 2 , stabilizer, and Nb 2 O 5 The content of each component is ZrO 2 , HfO 2 , stabilizer, and Nb 2 O 5 The content ratio is based on the total of 100 mol %.
[0040] The stabilizer content is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5When the total content of the capping element or ion and Nb is Bmol%, the ratio of A / B is preferably 0.9 or more and 3 or less, more preferably 0.95 or more and 2 or less, from the viewpoint of machinability. 2 O 5 and / or Ta 2 O 5 It is even more preferable that the ratio is 1 or more and 1.6 or less, because the combined effect of these factors is enhanced, better machinability can be imparted, wear on the machining tool can be suppressed, and the number of processed bodies obtained by continuous machining using one machining tool can be further increased.
[0041] In one preferred embodiment of the present invention, ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, further comprising a capping element or ion, The stabilizer is Y 2 O 3 and / or CeO 2 Including, The content of the capping element or ion is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta2 O 5 More than 0 mol% and 3 mol% or less relative to the total of 100 mol%. The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content of is B mol %, the black zirconia composite sintered body has an A / B ratio of 0.9 or more and 3 or less.
[0042] In one embodiment of the present invention, ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and a black zirconia composite sintered body further comprising a zirconia strengthening agent in addition to the capping element or ion. The zirconia reinforcement agent is ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 In the black zirconia composite sintered body containing the above, it acts integrally with the capping element or ion to improve the strength of the sintered body.
[0043] As mentioned above, in the black zirconia composite sintered body containing a zirconia reinforcement agent, ZrO 2 and HfO 2 Total content, type and content of stabilizer, Nb 2 O 5 and Ta 2 O 5 The total content, the type and content of the capping element or ion, and the ratio A / B can be appropriately changed.
[0044] In the black zirconia composite sintered body containing zirconia reinforcement, the content of the zirconia reinforcement is set to ZrO 2 and HfO 2and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and Ta 2 O 5 With respect to the total of 100 mass% of the above, the content is preferably more than 0 mass% and 5.0 mass% or less, and from the viewpoints that when combined with the capping element or ion, they act together to provide excellent machinability and strength, the content is more preferably 0.01 mass% or more and 4.5 mass% or less, and even more preferably 0.5 mass% or more and 4.0 mass% or less.
[0045] Zirconia reinforcement agents include TiO 2 , Al 2 O 3 The zirconia reinforcing agent may be used alone or in combination of two or more kinds.
[0046] In one preferred embodiment, the zirconia toughener is TiO 2 Contains TiO 2 The black zirconia composite sintered body has a content of 0.6 to 3.7 mass %.
[0047] In one preferred embodiment, ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O5 The total content of is 1 to 9 mol%, further comprising a capping element or ion, The stabilizer is Y 2 O 3 and / or CeO 2 Including, The zirconia reinforcement agent is TiO 2 Contains TiO 2 The content is 0.6 to 3.7 mass %, The content of the capping element or ion is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 More than 0 mol% and 3 mol% or less relative to the total of 100 mol%. The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content of is B mol %, the black zirconia composite sintered body has an A / B ratio of 0.9 or more and 3 or less.
[0048] The average crystal grain size of the black zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm, and even more preferably 1.0 to 4.0 μm, from the viewpoint of superior machinability and strength. The method for measuring the average crystal grain size is as described in the Examples below. The average crystal grain size can be measured by adjusting the number of particles so that the number of particles contained in one field of view of an SEM photograph is about 50 or 100, in the method described in the Examples.
[0049] The density of the black zirconia composite sintered body is set at 5.5 g / cm because the higher the density, the fewer the internal voids and the greater the strength. 3 It is preferable that the content is 5.7 g / cm or more. 3 More preferably, it is 5.9 g / cm or more. 3 More preferably, it is equal to or greater than this. It is particularly preferable that the black zirconia composite sintered body contains substantially no voids. The density of the compound sintered body can be calculated by (mass of the compound sintered body) / (volume of the compound sintered body).
[0050] In another embodiment of the present invention, ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In total 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, producing a molded body using a raw material composition further containing a capping agent; and sintering the green body.
[0051] The raw material composition used to manufacture the black zirconia composite sintered body is ZrO 2 and HfO 2 and a stabilizer capable of suppressing the phase transition of zirconia, and Nb 2 O 5 and / or Ta 2 O 5and a capping agent. The raw material composition of the black zirconia composite sintered body may be in a dry state, or may be in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, a powder, a granule or a granulated material, a paste, a slurry, or the like.
[0052] The raw material composition contains a capping agent so that the resulting black zirconia composite sintered body contains a capping element or ion. The capping agent is not particularly limited as long as it is a compound that can become a monovalent ion (a +1-valent cation or a -1-valent anion) in a solvent containing water, and examples thereof include hydroxides, salts, halides (fluorides, chlorides, bromides, iodides), cyanides, etc., containing an element or ion derived from the capping agent. Each of the capping agents may be used alone or in combination of two or more.
[0053] Examples of hydroxides containing capping elements or ions include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, francium hydroxide, and the like. Salts containing capping elements or ions include, for example, carbonates, bicarbonates, nitrates, hypochlorites, chlorites, chlorates, perchlorates, bromates, permanganates, metaborates, sulfide salts, and cyanide salts.
[0054] Examples of carbonates containing capping elements or ions include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, cesium carbonate, and the like. Examples of hydrogen carbonates containing a capping element or ion include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate. Examples of nitrates containing capping elements or ions include calcium nitrate, strontium nitrate, iron (II) nitrate, iron (III) nitrate, cobalt (II) nitrate, magnesium nitrate, gallium nitrate, yttrium (III) nitrate, lanthanum (III) nitrate, praseodymium nitrate, neodymium (III) nitrate, manganese (II) nitrate, europium nitrate, copper (II) nitrate, thorium nitrate, aluminum nitrate, nickel (II) nitrate, chromium (III) nitrate, titanium (IV) nitrate, zirconium nitrate, zirconium oxynitrate (IV) hydrate (ZrO(NO 3 ) 2 xH 2 O), cerium(III) nitrate, tin nitrate, bismuth(III) nitrate, scandium(III) nitrate, indium(III) nitrate, hafnium(IV) nitrate, etc. Hypochlorites containing capping elements or ions include, for example, sodium hypochlorite, calcium hypochlorite, and the like. Examples of chlorites containing a capping element or ion include sodium chlorite, potassium chlorite, lithium chlorite, calcium chlorite, magnesium chlorite, barium chlorite, copper(II) chlorite, copper(III) chlorite, silver chlorite, nickel chlorite, and the like. Chlorates containing capping elements or ions include, for example, calcium chlorate, barium chlorate, cobalt chlorate, nickel chlorate, magnesium chlorate, zinc chlorate, copper chlorate, and the like. Perchlorates containing capping elements or ions include, for example, iron (III) perchlorate, barium perchlorate, calcium perchlorate, cobalt perchlorate, nickel perchlorate, magnesium perchlorate, beryllium perchlorate, aluminum perchlorate, and cerium perchlorate. Bromates containing capping elements or ions include, for example, neodymium bromate, lanthanum bromate, praseodymium bromate, and the like. Permanganates containing capping elements or ions include, for example, calcium (VII) permanganate, potassium (VII) permanganate, sodium (VII) permanganate, and the like. Metaborates containing capping elements or ions include, for example, sodium metaborate, barium metaborate, and the like. Sulfide salts containing capping elements or ions include, for example, copper(I) sulfide. Cyanide salts containing capping elements or ions include, for example, barium cyanide, sodium cyanide, potassium cyanide, calcium cyanide, and the like.
[0055] Examples of fluorides containing capping elements or ions include lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, cesium fluoride, francium fluoride, beryllium fluoride, magnesium fluoride, calcium fluoride, strontium fluoride, barium fluoride, scandium (III) fluoride, yttrium (III) fluoride, lanthanum (III) fluoride, cerium (III) fluoride, neodymium (I) fluoride, and fluoride containing ions such as fluoride, ... II), titanium fluoride (III), titanium fluoride (IV), zirconium fluoride (IV), hafnium fluoride (IV), tantalum fluoride (V), manganese fluoride (II), manganese fluoride (III), iron fluoride (II), iron fluoride (III), copper fluoride (II), zinc fluoride (II), aluminum fluoride, chromium fluoride (III), bismuth fluoride (III), indium fluoride (III), tin fluoride (II), and the like.
[0056] Examples of chlorides containing capping elements or ions include zirconium oxychloride, lithium chloride, sodium chloride, potassium chloride, rubidium chloride, cesium chloride, francium chloride, beryllium chloride, magnesium chloride, calcium chloride, strontium chloride, barium chloride, scandium chloride (III), yttrium chloride (III), lanthanum chloride (III), cerium chloride (III), praseodymium chloride, neodymium chloride (III), samarium chloride, europium chloride, titanium chloride (III), titanium chloride (IV), zirconium chloride (IV), hafnium chloride (IV), tantalum chloride (V), manganese chloride, iron chloride (II), iron chloride (III), cobalt chloride (II), nickel chloride (II), copper chloride (I), copper chloride (II), zinc chloride (II), aluminum chloride, gallium chloride, bismuth chloride (III), indium chloride (I), indium chloride (III), and tin chloride (II).
[0057] Examples of bromides containing capping elements or ions include lithium bromide, sodium bromide, potassium bromide, rubidium bromide, cesium bromide, francium bromide, beryllium bromide, magnesium bromide, calcium bromide, strontium bromide, barium bromide, scandium (III) bromide, yttrium (III) bromide, cerium (III) bromide, neodymium (III) bromide, titanium (IV) bromide, zirconium (IV) bromide, tantalum (V) bromide, manganese (II) bromide, iron (II) bromide, iron (III) bromide, cobalt (II) bromide, nickel (II) bromide, copper (I) bromide, copper (II) bromide, zinc (II) bromide, chromium (III) bromide, bismuth (III) bromide, vanadium (III) bromide, indium (III) bromide, and tin bromide.
[0058] Examples of iodides containing capping elements or ions include lithium iodide, sodium iodide, potassium iodide, rubidium iodide, cesium iodide, francium iodide, beryllium iodide, calcium iodide, magnesium iodide, strontium iodide, barium iodide, scandium (III) iodide, yttrium (III) iodide, lanthanum (III) iodide, cerium (III) iodide, neodymium (III) iodide, titanium (IV) iodide, ), zirconium iodide (IV), hafnium iodide (IV), tantalum iodide (V), manganese iodide (II), iron iodide (II), iron (III), cobalt iodide (II), nickel iodide (II), copper iodide (I), zinc iodide (II), aluminum iodide, chromium iodide (III), vanadium iodide (II), bismuth iodide (III), indium iodide (III), tin iodide (II), and tin iodide (IV).
[0059] ZrO 2 and HfO 2 For the above, commercially available zirconia powder can be used. For example, zirconia powder (trade name "Zpex (registered trademark)" (Y 2 O 3 Content of Y: 3 mol%), "Zpex (registered trademark) 4" 2 O 3 Content of 4 mol%), "Zpex (registered trademark) 4 Smile (registered trademark)" 2 O 3 content: 5.5mol%), "TZ-3Y" (Y 2 O 3 content: 3mol%), "TZ-3YS" (Y 2 O 3 content: 3mol%), "TZ-4YS" (Y 2 O 3 content: 4 mol%), "TZ-6Y" (Y 2 O 3 Content: 6 mol%), "TZ-6YS" (Y 2 O 3 content: 6 mol%), "TZ-8YS" (Y 2 O 3content: 8 mol%), "TZ-10YS" (Y 2 O 3 content: 10mol%), "TZ-3Y-E" (Y 2 O 3 content: 3mol%), "TZ-3YS-E" (Y 2 O 3 content: 3mol%), "TZ-3YB-E" (Y 2 O 3 content: 3mol%), "TZ-3YSB-E" (Y 2 O 3 content: 3mol%), “TZ-3YB” (Y 2 O 3 content: 3mol%), "TZ-3YSB" (Y 2 O 3 content: 3mol%), “TZ-3Y20AB” (Y 2 O 3 content: 3 mol%), "TZ-8YSB" (Y 2 O 3 content: 8 mol%), "TZ-0" (Y 2 O 3 The commercially available zirconia powder includes HfO 2 Also included are Y 2 O 3 As the zirconia powder, the raw material composition of the present invention may contain zirconia powder containing Y, such as the commercially available TZ series (part of the product name includes "TZ"). 2 O 3 It is also possible to use a zirconia powder in which the above is uniformly dispersed and solid-dissolved.
[0060] There are no particular limitations on the method for producing the zirconia powder, and any known method can be used, such as a breakdown process in which coarse particles are pulverized into fine powder, or a building-up process in which atoms or ions are synthesized through a nucleation and growth process.
[0061] The type of zirconia powder in the raw material composition is not particularly limited, and the zirconia powder is ZrO 2 and HfO2 In the case where the stabilizer is not included or the content of the stabilizer is increased as required, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the black zirconia composite sintered body can be adjusted to the above-mentioned predetermined range. The particles of the stabilizer may be, for example, a commercially available product, or a powder of the commercially available product may be ground in a known grinding and mixing device (such as a ball mill) before use.
[0062] The stabilizer is ZrO 2 and HfO 2 Stabilizer that is not dissolved in solid solution, ZrO 2 and HfO 2 Any of the stabilizers that are solid-soluble in the composition can be used. In a preferred embodiment, the raw material composition contains a stabilizer (preferably, Y 2 O 3 ) but ZrO 2 and HfO 2 The fact that the stabilizer is not solid-dissolved in zirconia can be confirmed, for example, by an X-ray diffraction (XRD) pattern.
[0063] When a peak derived from a stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, it is considered that ZrO 2 and HfO 2 This means that there is stabilizer that is not dissolved in the solid solution. The total amount of stabilizer is ZrO 2 and HfO 2 When the stabilizer is dissolved in ZrO, basically, no peaks due to the stabilizer are observed in the XRD pattern. However, depending on the conditions such as the crystal state of the stabilizer, even if there are no stabilizer peaks in the XRD pattern, it may be possible that the stabilizer is ZrO 2 and HfO 2It is possible that the ferroelectric material is not solid-dissolved in the ferroelectric material.
[0064] The stabilizer is ZrO 2 and HfO 2 The case where a stabilizer that is not solid-dissolved in the glass is contained will be described below by taking yttria as an example of the stabilizer.
[0065] In the raw material composition or molded article of the present invention, ZrO 2 and HfO 2 The abundance rate of yttria that is not dissolved in the y can be calculated based on the following formula (1). f y =I 29 / (I 28 +I 29 +I 30 ) x 100 (In the formula, f y represents the percentage of undissolved yttria (%). In the XRD measurement, I 28 represents the integrated intensity of the peak at 2θ = 28° where the main monoclinic peak appears, and I 29 represents the intensity of the peak at 2θ = 29° where the main peak of yttria appears, and I 30 represents the integrated intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic crystal system appears.)
[0066] In addition, when a stabilizer other than yttria is used, I 29 By substituting the peak of another stabilizer instead of yttria, the above formula can also be applied to calculate the undissolved fraction of stabilizers other than yttria.
[0067] Undissolved yttria abundance f y From the viewpoint of easily obtaining the desired black zirconia composite sintered body, the content of undissolved yttria f is preferably more than 0%, more preferably 1% or more, even more preferably 2% or more, and particularly preferably 3% or more. yThe upper limit may be, for example, 25% or less, but preferably depends on the content of yttria in the raw material composition or the molded body.
[0068] For example, when the content of yttria in the raw material composition or molded article of the present invention is 3 mol % or more and 8 mol % or less, the following applies. When the yttria content is 3 mol% or more and less than 4.5 mol%, f y When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y When the yttria content is 5.8 mol% or more and 8 mol% or less, f y may be no more than 25%.
[0069] For example, when the yttria content is 3 mol% or more and less than 4.5 mol%, f y is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y is preferably 3% or more, more preferably 4% or more, even more preferably 5% or more, even more preferably 6% or more, and particularly preferably 7% or more. When the yttria content is 5.8 mol% or more and 8 mol% or less, f y is preferably 4% or more, more preferably 5% or more, even more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more.
[0070] In the raw material composition or molded article of the present invention, the entire stabilizer is ZrO 2 and HfO 2 In the present invention, the term "the stabilizer is solid-dissolved" means that, for example, an element (atom) contained in the stabilizer is ZrO 2 and HfO 2This means that the material dissolves in a solid solution.
[0071] The Nb added to the raw material composition of the present invention 2 O 5 and / or Ta 2 O 5 is the Nb contained in the black zirconia composite sintered body. 2 O 5 and / or Ta 2 O 5 The content of Nb is not particularly limited as long as it can be adjusted to the above-mentioned range. 2 O 5 and / or Ta 2 O 5 is not particularly limited, and for example, a commercially available product may be used, or a powder of the commercially available product may be ground with a known grinding and mixing device (such as a ball mill) before use.
[0072] The step of preparing the raw material composition may, for example, be carried out by mixing each raw material of the raw material composition (ZrO 2 and HfO 2 and a stabilizer, Nb 2 O 5 and / or Ta 2 O 5 and a method of wet-mixing a zirconia reinforcing agent (e.g., a compound that can become a monovalent ion in a solvent containing water) and, if necessary, a zirconia reinforcing agent) in a solvent containing water to obtain a raw material composition.
[0073] The method for wet-mixing the raw materials in a solvent containing water is not particularly limited. For example, the raw materials may be wet-pulverized and mixed in a known pulverizing and mixing device (such as a ball mill) to form a slurry, and then the slurry may be dried and granulated to produce a granular raw material composition.
[0074] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, an antifoaming agent, a pH adjuster, a lubricant, etc. may be further included. Each of the additives may be used alone or in combination of two or more kinds.
[0075] The binder is ZrO 2 and HfO2 And, Y 2 O 3 and Nb 2 O 5 and / or Ta 2 O 5 Alternatively, the primary powder consisting of the mixture of the cellulose acetate and the capping agent may be added to water to form a slurry, and then the pulverized powder may be added to the slurry.
[0076] The binder is not particularly limited, and known binders can be used. Examples of binders include polyvinyl alcohol binders, acrylic binders, wax binders (paraffin wax, etc.), methyl cellulose, carboxymethyl cellulose, polyvinyl butyral, polymethyl methacrylate, ethyl cellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymers, polystyrene, atactic polypropylene, and methacrylic resins.
[0077] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.
[0078] Examples of dispersants include ammonium polycarboxylate (e.g., triammonium citrate), ammonium polyacrylate, acrylic copolymer resin, acrylic acid ester copolymer, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate), nonionic surfactants, olein glyceride, amine salt surfactants, oligosaccharide alcohols, and stearic acid.
[0079] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.
[0080] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.
[0081] Examples of pH adjusters include ammonia, ammonium salts (including ammonium hydroxides such as tetramethylammonium hydroxide), and the like.
[0082] Examples of the lubricant include polyoxyethylene alkyl ether and wax.
[0083] The solvent used in the wet mixing is not particularly limited as long as it contains water, and an organic solvent may be used, a mixed solvent of water and an organic solvent may be used, or only water may be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; and alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerin, diglycerin, polyglycerin, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.
[0084] The raw material composition of the black zirconia composite sintered body used in the present invention is ZrO 2 , Y 2 O 3 , Nb 2 O 5 , Ta 2 O 5 The composition may contain other components besides the zirconia reinforcing agent, such as colorants (pigments and composite pigments), fluorescent agents, SiO 2 The other components may be used alone or in combination of two or more.
[0085] The pigment may be, for example, an oxide of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr 2 O3 and the like), and an oxide of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb is preferred, and an oxide of at least one element selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb is more preferred. However, from the pigments, Y 2 O 3 and CeO 2 may be excluded.
[0086] Examples of the composite pigment include (Zr, V)O 2 , Fe(Fe,Cr) 2 O 4 , (Ni,Co,Fe)(Fe,Cr) 2 O 4 ZrSiO 4 , (Co,Zn)Al 2 O 4 etc.
[0087] The fluorescent agent may be, for example, Y 2 SiO 5 : Ce, Y 2 SiO 5 :Tb, (Y,Gd,Eu)BO 3 , Y 2 O 3 :Eu, YAG:Ce, ZnGa 2 O 4 :Zn, BaMgAl 10 O 17 :Eu, etc.
[0088] Next, the obtained raw material composition is molded to prepare a molded body. The molding method is not particularly limited, and a known method (for example, press molding, etc.) can be used.
[0089] In the case of producing a zirconia molded body by a method having a step of press-molding a raw material composition, the specific method of press molding is not particularly limited, and can be performed using a known press molding machine. Specific examples of the press molding method include uniaxial pressing.
[0090] The pressing pressure is set to an appropriate optimum value depending on the size, open porosity, biaxial bending strength, and particle size of the raw material powder of the target molded body, and is usually 5 MPa to 1000 MPa. By increasing the pressing pressure during molding in the above-mentioned manufacturing method, the pores of the obtained molded body are filled more, the open porosity can be set low, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, a cold isostatic pressing (CIP) treatment may be further performed after uniaxial pressing.
[0091] Next, the resulting green body is sintered. The term "molded body" refers to a body that has not yet reached a semi-sintered state (calcined state) or a sintered state. In other words, the molded body is distinguished from the calcined body and the sintered body in that the molded body is a body that has been molded and then not sintered. The sintering temperature (maximum sintering temperature) for obtaining the black zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, even more preferably 1400°C or higher, even more preferably 1450°C or higher, and particularly preferably 1500°C or higher. The sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and even more preferably 1600°C or lower. In the method for producing the black zirconia composite sintered body of the present invention, it is preferable to sinter the molded body at a maximum sintering temperature of 1400 to 1680°C. The maximum sintering temperature is preferably a temperature in the atmosphere.
[0092] The holding time (holding time) at the maximum sintering temperature depends on the temperature, but is preferably 30 hours or less, more preferably 20 hours or less, even more preferably 10 hours or less, even more preferably 5 hours or less, particularly preferably 3 hours or less, and most preferably 2 hours or less. Furthermore, the holding time can be 25 minutes or less, 20 minutes or less, or 15 minutes or less. Moreover, the holding time is preferably 1 minute or more, more preferably 5 minutes or more, and even more preferably 10 minutes or more. According to the manufacturing method of the present invention, a black zirconia composite sintered body excellent in bending strength and machinability can be produced depending on the content of the stabilizer. Moreover, the sintering time may be shortened as long as the effect of the present invention can be obtained. By shortening the sintering time, it is possible to increase production efficiency and reduce energy costs.
[0093] In the method for producing a black zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, and is preferably 0.1° C. / min or more, more preferably 0.2° C. / min or more, and even more preferably 0.5° C. / min or more. The heating rate is preferably 50° C. / min or less, more preferably 30° C. / min or less, and even more preferably 20° C. / min or less. When the heating rate is equal to or more than the lower limit, productivity is improved.
[0094] A general zirconia firing furnace can be used in the step of sintering the molded body. Commercially available zirconia firing furnaces may be used. Examples of commercially available zirconia firing furnaces include Noritake Katana (registered trademark) F-1, F-1N, and F-2 (all manufactured by SK Medical Electronics Co., Ltd.).
[0095] In the method for producing a black zirconia composite sintered body, a black zirconia composite sintered body can also be obtained by sintering a green body to which a black pigment has been added. Examples of black pigments include black organic pigments, mixed color organic pigments, and inorganic pigments. Examples of black organic pigments include carbon black, perylene black, aniline black, benzofuranone pigments, etc. These may be coated with a resin. The mixed color organic pigments include, for example, pigments obtained by mixing two or more kinds of pigments such as red, blue, green, purple, yellow, magenta, and / or cyan to produce a pseudo-black color. Examples of black inorganic pigments include graphite; fine particles of metals such as titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, and silver; metal oxides; metal composite oxides; metal sulfides; metal nitrides; metal oxynitrides; and metal carbides. However, when using a pigment containing titanium as a black pigment, the total titanium content must be less than the TiO 2 It is preferable that the upper limit of the content of 5.0 mass % is not exceeded.
[0096] In addition to or instead of the method of adding a black pigment to the green body, it is preferable to subject the green body to reduction firing in addition to sintering at the above-mentioned maximum sintering temperature. In one preferred embodiment, the step of sintering the compact includes a step of reducing and firing the compact in addition to the sintering at the maximum sintering temperature.
[0097] The reduction firing step is not particularly limited as long as it is sintered under a reducing atmosphere, but for example, a step of hot isostatic pressing (HIP) treatment in a reducing atmosphere can be mentioned. By the HIP treatment under a reducing atmosphere, blackening occurs due to oxygen defects, and a black zirconia compound sintered body can be obtained. In addition, the strength of the black zirconia compound sintered body can be further improved by the HIP treatment.
[0098] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after the HIP treatment is referred to as a "HIP-treated sintered body".
[0099] The HIP treatment can be carried out using a known hot isostatic press (HIP) device.
[0100] The temperature of the HIP treatment is not particularly limited, but since a dense black zirconia composite sintered body with high strength can be obtained, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and even more preferably 1400° C. or higher. The HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and even more preferably 1600° C. or lower.
[0101] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited, and since a dense sintered body with high strength can be obtained, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and even more preferably 130 MPa or more. The upper limit of the HIP pressure is not particularly limited, but can be, for example, 400 MPa or less, 300 MPa or less, or even 200 MPa or less.
[0102] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, and is preferably 0.1° C. / min or more, more preferably 0.2° C. / min or more, and even more preferably 0.5° C. / min or more. The heating rate is preferably 50° C. / min or less, more preferably 30° C. / min or less, and even more preferably 20° C. / min or less. The heating rate is equal to or higher than the lower limit, thereby improving productivity.
[0103] In the method for producing the black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to the HIP treatment, the HIP time is not particularly limited, and since a dense black zirconia composite sintered body having high strength can be obtained, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. Also, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.
[0104] In the method for producing a black zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment in a reducing atmosphere, the pressure medium is not particularly limited, and from the viewpoint of having little effect on zirconia, the pressure medium can be at least one selected from the group consisting of inert gases (e.g., nitrogen, argon, etc.).
[0105] In the step of performing the reducing and sintering, it is preferable to perform the reducing and sintering in the presence of carbon, since this increases the efficiency of the sintering in a reducing atmosphere, reduces the L* value of the composite sintered body, and produces a black zirconia composite sintered body with a deeper color. The carbon used in the reduction and firing step is not particularly limited, and examples thereof include Referthermo (a common thermal history sensor, containing a small amount of organic components (organic binder (PVA / PEG type))).
[0106] The black zirconia composite sintered body of the present invention is not particularly limited as long as it exhibits the effects of the present invention, and may be a primary sintered body or a HIP-treated sintered body.
[0107] Although the black zirconia composite sintered body of the present invention is a sintered body, it has excellent machinability, so there is no need to machine the semi-sintered calcined body in the form of a mill blank and then sinter it to form a sintered body. On the other hand, the method for producing the black zirconia composite sintered body may also be a method in which a molded body obtained by using the raw material composition is calcined to produce a calcined body in a semi-sintered state, and the unprocessed calcined body is mechanically processed to produce a sintered body.
[0108] In another embodiment, the method includes the steps of: preparing a molded body using the raw material composition; calcining the obtained molded body to obtain a calcined zirconia body (calcination step); and sintering the calcined zirconia body. A method for producing a black zirconia composite sintered body can be mentioned.
[0109] In order to ensure blocking, the firing temperature (calcination temperature) in the calcination step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and even more preferably 950° C. or higher. The calcination temperature is, for example, preferably 1200° C. or lower, more preferably 1150° C. or lower, and further preferably 1100° C. or lower. The calcination temperature is, for example, preferably 800° C. to 1200° C. At such a calcination temperature, it is considered that the dissolution of the stabilizer does not progress significantly in the calcination step.
[0110] The zirconia calcined body of the present invention is ZrO 2 The particles are necked together (adhered together), and ZrO 2 This means that the particles (powder) are in a state where they are not completely sintered (semi-sintered state).
[0111] The density of the calcined zirconia body is 2.7 g / cm 3 The density of the calcined zirconia body is preferably 4.0 g / cm 3 Less than 3.8 g / cm is preferred. 3 Less than 3.6 g / cm is more preferable. 3 The following is even more preferable. When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, by dividing the mass of the calcined body by the volume of the calcined body.
[0112] The three-point bending strength of the zirconia calcined body is preferably from 15 to 70 MPa, more preferably from 18 to 60 MPa, and even more preferably from 20 to 50 MPa. The bending strength can be measured using a test piece having a thickness of 5 mm, a width of 10 mm, and a length of 50 mm, in accordance with ISO 6872:2015, except for the size of the test piece. The face of the test piece and the C face (the face of the test piece with the corners chamfered at an angle of 45°) are surface-finished in the longitudinal direction with 600-grit sandpaper. The test piece is arranged so that the widest face faces vertically (load direction). In the bending test measurement, the span is 30 mm, and the crosshead speed is 1.0 mm / min.
[0113] The step of sintering the zirconia calcined body can be carried out by the same method and under the same conditions (temperature, pressure, etc.) as the step of sintering the molded body described above. Therefore, in the embodiment of the production method using the zirconia calcined body, the "molded body" can be read as the "calcined body".
[0114] The black zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the black zirconia composite sintered body of the present invention is preferably 300 MPa or more, more preferably 350 MPa or more, even more preferably 400 MPa or more, even more preferably 450 MPa or more, and particularly preferably 500 MPa or more. When the black zirconia composite sintered body of the present invention has such a biaxial bending strength, for example, breakage can be suppressed. There is no particular limit to the upper limit of the biaxial bending strength, but the biaxial bending strength can be, for example, 1200 MPa or less, or even 1000 MPa or less. The biaxial bending strength of the black zirconia composite sintered body can be measured in accordance with ISO 6872:2015.
[0115] The black zirconia composite sintered body of the present invention preferably has a desired color tone in terms of excellent design. The color tone can be evaluated by L*, |a*|, and |b*|. L*, |a*| and |b*| can be calculated by measuring L*, a* and b* according to the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) on a measurement sample with a diameter of 15 mm and a thickness of 1.2 mm, and then using, for example, a spectrophotometer "CM-3610A" manufactured by Konica Minolta, Inc. under conditions of a D65 light source, measurement mode SCI, and measurement diameter / illumination diameter = φ8mm / φ11mm.
[0116] Regarding color tone, specifically, in the black zirconia composite sintered body of the present invention, when a sample having a diameter of 15 mm and a thickness of 1.2 mm is placed against a white background (underlay) (the side of the sample opposite to the color tone measuring device is placed in white), L* is preferably 60 or less, more preferably 55 or less, and even more preferably 50 or less. In addition, in the above-mentioned samples and measurement conditions, |a*| is preferably 3 or less, more preferably 2 or less, and even more preferably 1 or less. Furthermore, in the above-mentioned sample and measurement conditions, |b*| is preferably 3 or less, more preferably 2.5 or less, and even more preferably 2 or less. As a preferred embodiment, there can be mentioned a black zirconia composite sintered body in which, under the above-mentioned sample and measurement conditions, L* is 60 or less, |a*| is 3 or less, and |b*| is 3 or less. Another preferred embodiment is a black zirconia composite sintered body in which, under the above-mentioned sample and measurement conditions, L* is 50 or less, |a*| is 1 or less, and |b*| is 2 or less. When the L*, |a*|, and |b*| are within the above ranges, a black zirconia composite sintered body having excellent design properties can be obtained.
[0117] One preferred embodiment, from the viewpoint of easily obtaining superior design properties, is a black zirconia composite sintered body in which the colorimetric values measured on a sample having a diameter of 15 mm and a thickness of 1.2 mm against a white background using the L*a*b* color system are L*≦60, |a*|≦3, and |b*|≦3.
[0118] In view of excellent designability, the black zirconia composite sintered body of the present invention has a color tone in which a sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background according to the L*a*b* color system. The color saturation C* calculated from a* and b* is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. C* is a* obtained by the above method, and b * The average value of chroma C * =((a * ) 2 +(b * ) 2 ) 1 / 2 can be calculated.
[0119] The coefficient of thermal expansion (CTE) of the black zirconia composite sintered body of the present invention is 8×10 -6 / ℃~13×10 -6 / °C, and preferably 8.5×10 -6 / ℃~12×10 -6 / °C, more preferably 9×10 -6 / ℃~11×10 -6 / °C. is even more preferred. Since the black zirconia composite sintered body of the present invention has a coefficient of thermal expansion (CTE) within the above range, it can be suitably used in combination with metal materials. The coefficient of thermal expansion (CTE) can be measured in accordance with ISO 6872:2015, with the analysis temperature range being 25° C. to 500° C., and the measurement can be performed at a heating rate of, for example, 5° C. / min.
[0120] Furthermore, the black zirconia composite sintered body of the present invention is particularly suitable for use in zirconia members that require a special or complicated shape and strength. Compared with sintered bodies manufactured only by existing manufacturing methods (injection molding, CIP, slip casting, 3D printing, etc.), the black zirconia composite sintered body of the present invention can be processed as it is. Therefore, for example, it is economical when a desired zirconia part can be obtained in a short time, and in the case of a complex-shaped part that is difficult to manufacture by conventional manufacturing methods, it is possible to obtain a zirconia part that maintains high strength because there is no need to obtain multiple parts by mechanical fitting. Furthermore, since the sintered body can be processed as it is, a sintering process is not required when dimensional accuracy is required, and since there is no uneven firing shrinkage, a zirconia part can be obtained with high accuracy. In addition, machining can be performed using, for example, a commercially available machining device.
[0121] Specific applications of the black zirconia composite sintered body of the present invention include jewelry applications (brooches, tie pins, handbag fittings, bracelets, etc.), engine parts and interior parts for mobility such as aircraft and automobiles, display panel frames, building parts, portable device parts, luxury daily use parts, watch parts (watch bands, bezels, dials, watch cases, etc.), exterior parts such as housings for portable electronic devices (e.g., smartphones), lighter cases, cosmetic cases, mobile phone cases, and earphone housings, electrical appliance parts, household product parts, logo marks for various products, and toy parts. The zirconia member may also be fitted with a different material to be used as a composite member.
[0122] The present invention includes embodiments in which all or part of the above configurations are combined in various ways within the scope of the technical idea of the present invention, as long as the effects of the present invention are achieved. EXAMPLES
[0123] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples, and many modifications within the scope of the technical concept of the present invention are possible by those having ordinary skill in the art. In the following examples and comparative examples, the average particle size refers to the average primary particle size, which can be determined by a laser diffraction scattering method. Specifically, it can be measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) with a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium.
[0124] [Examples 1 to 17 and Comparative Examples 1 to 4] The measurement samples of each of the Examples and Comparative Examples were prepared through the steps of preparing a granular raw material composition, preparing a compact, and preparing a sintered body (preparation of a primary sintered body, and HIP treatment).
[0125] [Preparation of granular raw material composition] In order to prepare the granular raw material compositions of each of the Examples and Comparative Examples, commercially available ZrO 2 powder, Y 2 O 3 powder, Nb 2 O 5 Powder, Ta 2 O 5 powder, and capping agent, and optionally zirconia reinforcement powder (TiO 2 Powder and / or Al 2 O 3 Powder) were mixed to the composition shown in Tables 1 and 2, water was added to prepare a slurry, and the mixture was wet-pulverized and mixed in a ball mill until the average particle size was 0.13 μm or less. A binder was added to the pulverized slurry, which was then dried with a spray dryer to prepare a granular raw material composition (hereinafter, also simply referred to as the "raw material composition"), which was used in the manufacture of a molded body described below. The average particle size was measured on a volume basis using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) with a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium. In Example 17, TZ-3Y (Y 2 O 3Content of: 3 mol%): TZ-6Y (Y 2 O 3 The content of each component was adjusted to be the blending ratio shown in Table 1.
[0126] [Preparation of molded body] For each of the Examples and Comparative Examples, pellet-shaped compacts and block-shaped compacts were prepared as follows so as to obtain sintered body samples for evaluating strength and workability. For the pellet-shaped compact, a cylindrical mold having a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the black zirconia composite sintered body after sintering would be 1.2 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a pellet-shaped compact.
[0127] For the block-shaped compact, the raw material composition was placed in a metal mold having an inner dimension of 19 mm×18 mm so that the height of the black zirconia composite sintered body after sintering would be 14.5 mm. Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a block-shaped compact.
[0128] [Preparation of primary sintered body] The pellet-shaped and block-shaped compacts obtained were subjected to a firing furnace "Noritake Katana (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., and were held in the atmosphere for 2 hours at the firing temperatures shown in Tables 1 and 2 to obtain pellet-shaped and block-shaped zirconia sintered body (primary sintered body) samples.
[0129] [Production of black zirconia composite sintered body (HIP-treated sintered body)] The pellet-shaped and block-shaped zirconia sintered bodies (primary sintered bodies) obtained were subjected to HIP processing using the "O 2Using "Dr.HIP" and argon gas as the pressure medium, samples of black zirconia composite sintered body (HIP-treated sintered body) in pellet and block shapes were obtained by holding for 2 hours at 150 MPa with the HIP temperature and with or without Refer Thermo as shown in Tables 1 and 2. The pellet-shaped samples were 15 mm in diameter x 1.2 mm in thickness, and the block-shaped samples were 15.7 mm in width x 16.5 mm in length x 14.5 mm in height.
[0130] The content of each component of the sintered body in Tables 1 and 2 is a value calculated from the amount of raw material charged. The capping element or ion contents (mol%) in Tables 1 and 2 are ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The external addition rate is based on a total of 100 mol%. ZrO in Tables 1 and 2 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The respective contents (mol%) of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The content of each component is 100 mol% in total. ZrO 2 and HfO 2 Only for ZrO 2 and HfO 2 The total content is expressed as a percentage. TiO in Tables 1 and 2 2 and Al 2 O 3 The content (mass%) of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5The external addition rate is based on the total of 100 mass %. A / B in Tables 1 and 2 is Y 2 O 3 The content of Nb is Amol%, 2 O 5 and Ta 2 O 5 This represents the ratio of A to B when the total content of A and B is Bmol%.
[0131] [Color evaluation of black zirconia composite sintered body] The pellet-shaped black zirconia composite sintered body (HIP-treated sintered body) samples (diameter about 15 mm×thickness 1.2 mm) of each of the Examples and Comparative Examples were used as they were to evaluate the color tone by the following method (n=3). Using a spectrophotometer "CM-3610A" manufactured by Konica Minolta, Inc., L*, a*, and b* were measured using the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry - Part 4: CIE 1976 L*a*b* color space) with a D65 light source, measurement mode SCI, measurement diameter / illumination diameter = φ8mm / φ11mm, and the background (underlay) of the sample being white (the side opposite the measurement device with respect to the sample being white). The white background (underlay) used in the measurements was a hiding power test paper used in paint measurements as described in JIS K 5600-4-1:1999. The average values of L*, a*, and b* for each sample are shown in Tables 1 and 2.
[0132] [Strength evaluation of black zirconia composite sintered body] The biaxial bending strength of the pellet-shaped black zirconia composite sintered body (HIP-treated sintered body) samples of each Example and Comparative Example was measured as is using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) at a crosshead speed of 1.0 mm / min in accordance with ISO6872:2015 (n=5). The average values are shown in Tables 1 and 2 as the measurement results. A strength of 300 MPa or more was considered to be acceptable.
[0133] [Method for measuring average crystal grain size in sintered body] For each of the pellet-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of the Examples and Comparative Examples, images of the surfaces were taken with a scanning electron microscope (product name "VE-9800", manufactured by Keyence Corporation). After the grain boundaries of each crystal grain were recorded on the obtained images, the average crystal grain size was calculated by image analysis. The average crystal grain size was measured using image analysis software (product name "Image-Pro Plus", manufactured by Hakuto Co., Ltd.), the captured SEM image was binarized, the brightness range was adjusted so that the grain boundaries were clear, and the particles were recognized from the field of view (area). The crystal grain size obtained with Image-Pro Plus was the average of the lengths of the line segments connecting the outlines passing through the center of gravity determined from the outlines of the crystal grains, measured at intervals of two degrees from the center of gravity, and the average value of the crystal grain size of all the particles not overlapping the edge of the image in the SEM photograph images (three fields of view) of each Example and Comparative Example was taken as the average crystal grain size (number basis) in the sintered body. "Particles not on the image edge" refers to particles excluding those whose outlines do not fit within the screen of the SEM photograph (particles whose outlines end at the top, bottom, left, and right boundaries). The crystal grain size of all particles not on the image edge was determined by selecting the option to exclude all particles on the boundary lines in Image-Pro Plus.
[0134] The average crystal grain size of the crystal grains in the black zirconia composite sintered body of Example 3 was 2.7 μm, and the average crystal grain size of the crystal grains in the black zirconia composite sintered body of Example 8 was 2.2 μm.
[0135] [Evaluation of workability of black zirconia composite sintered body] Thirty samples of block-shaped black zirconia composite sintered bodies (HIP-treated sintered bodies) of each Example and Comparative Example were prepared by attaching a metal jig to a surface of about 15.7 mm wide x 14.5 mm high, and processed into a general anterior tooth crown shape using a CEREC system "MC-XL" (manufactured by Dentsply Sirona). Although the present invention is not specifically intended for dental use, the method is suitable for evaluating the degree of workability of sintered bodies in terms of both processing time and number of pieces, so the processing test was performed on an anterior tooth shape using a dental processing machine. The processing program used was the software "inLab (registered trademark) CAM version 20.0.1.203841", and the following settings were selected: Manufacturer: IVOCLAR VIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16, and the processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.
[0136] [Processing time] The processing times shown in Tables 1 and 2 are the times required to complete processing of the first sample using new processing tools under the conditions described in the above [Processability evaluation of black zirconia composite sintered body]. When not even one sample could be processed even after 120 minutes or more, it was marked as "X". In addition, if an error occurred due to the load during processing, etc., and the CEREC system "MC-XL" stopped midway through processing, a new processing tool was attached and processing was restarted. This operation was repeated until processing of one sample was completed, and the time required was recorded as the processing time.
[0137] [Number of pieces] The number of processed pieces shown in Tables 1 and 2 is the number of samples that could be processed into the shape of a front tooth crown without changing the processing tool once, using a new set of processing tools and starting processing of the samples under the conditions described in the above [Evaluation of the machinability of black zirconia composite sintered body]. The maximum number of samples used for the test was 30, and if processing of up to 30 samples could be completed with one processing tool, additional processing tests were not performed, and the number was uniformly set to "30 or more." Furthermore, if an error occurs due to the load during processing, etc., before the first sample is processed, and the MC-XL stops midway through processing, a new processing tool is attached and processing is resumed. This operation is repeated until one sample is processed, and the reciprocal of the number of processing tools used is taken as the number of processed samples. For example, "0.2 pieces" in Comparative Example 2 in Table 2 means that five processing tools were used to obtain a sample processed into the crown shape of one front tooth. The results are shown in Tables 1 and 2 below.
[0138] [Table 1]
[0139] [Table 2]
[0140] From the above results, it was confirmed that the black zirconia composite sintered body of the present invention has excellent machinability even though it is in a sintered state. It was also confirmed that the black zirconia composite sintered body of the present invention has suitable strength. In addition, in Examples 1 to 17, it was possible to suppress wear of the processing tool, and to increase the number of workpieces that can be continuously processed with one processing tool compared to the conventional technology. On the other hand, Nb 2 O 5 , and Ta 2 O 5 In Comparative Example 1, which did not contain any, machining was not possible. In Comparative Example 2, which did not contain any capping elements or ions, the reduction in processing time was not sufficient, and the number of processed pieces was also very small. In Comparative Example 3, which contained a divalent metal element that is not included in the capping elements, the reduction in processing time was not sufficient. In Comparative Example 4, which contained a trivalent metal element that is not included in the capping elements, the reduction in processing time was not sufficient.
[0141] In addition, TiO 2 Patent Document 4 shows that increasing the amount of Nb added reduces the strength in proportion to the amount of added (FIG. 7 of Patent Document 4). 2 O 5 and / or Ta 2 O 5 When the component is TiO, the TiO 2 It was confirmed from a comparison between Example 4 and Example 5 that the above components act together to improve the strength of the black zirconia composite sintered body. [Industrial Applicability]
[0142] The black zirconia composite sintered body of the present invention has excellent machinability and exhibits a black color with excellent designability. [Explanation of symbols]
[0143] 1 Zirconia particles 2. Peeling ingredients 3 Adhesive component 4 Grain boundaries where no exfoliation components exist
Claims
1. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, A black zirconia composite sintered body, further comprising elements or ions derived from a capping agent.
2. The content of the element or ion derived from the capping agent is ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 The black zirconia composite sintered body according to claim 1, wherein the content of each of the above is more than 0 mol% and 5 mol% or less with respect to a total of 100 mol%.
3. 3. The black zirconia composite sintered body according to claim 1, wherein a sample having a diameter of 15 mm and a thickness of 1.2 mm is used to measure the color of the sample against a white background in the L*a*b* color system, and the color saturation C* calculated from a* and b* is 10 or less.
4. 3. The black zirconia composite sintered body according to claim 1, wherein the colorimetric values of a sample having a diameter of 15 mm and a thickness of 1.2 mm measured against a white background in the L*a*b* color system satisfy L*≦60, |a*|≦3, and |b*|≦3.
5. The black zirconia composite sintered body according to any one of claims 1 to 4, wherein the element or ion derived from the capping agent contains at least one element or ion thereof selected from the group consisting of Cu, Ag, Li, Na, K, Rb, Cs, Fr, At, I, Br, Cl, and F.
6. The content of the stabilizer is expressed as Amol%, and Nb 2 O 5 and Ta 2 O 5 When the total content is B mol%, The black zirconia composite sintered body according to any one of claims 1 to 5, wherein A / B is 0.9 or more and 3 or less.
7. The stabilizer is Y 2 O 3 and / or CeO 2 The black zirconia composite sintered body according to any one of claims 1 to 6, comprising:
8. The composition further comprises a zirconia reinforcement agent, and the content of the zirconia reinforcement agent is ZrO 2 and HfO 2 and the stabilizer, and Nb 2 O 5 and Ta 2 O 5 The black zirconia composite sintered body according to any one of claims 1 to 7, wherein the content of the black zirconia composite sintered body is more than 0 mass% and 5.0 mass% or less with respect to the total 100 mass% of the above.
9. The zirconia reinforcement agent is TiO 2 And / or Al 2 O 3 The black zirconia composite sintered body according to claim 8, comprising:
10. The zirconia reinforcement agent is TiO 2 Including TiO 2 The black zirconia composite sintered body according to claim 9, wherein the content of is 0.6 to 3.7 mass%.
11. ZrO 2 and HfO 2 a stabilizer capable of suppressing the phase transition of zirconia; and Nb 2 O 5 And / or Ta 2 O 5 and ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 , and Ta 2 O 5 In a total of 100 mol%, ZrO 2 and HfO 2 The total content is 78 to 97.5 mol%, The content of the stabilizer is 1 to 12 mol %, Nb 2 O 5 and Ta 2 O 5 The total content of is 1 to 9 mol%, producing a molded body using a raw material composition further comprising a capping agent; and sintering the compact. The method for producing the black zirconia composite sintered body according to any one of claims 1 to 10.
12. The step of sintering the molded body includes a step of reducing and firing the molded body. The method for producing the black zirconia composite sintered body according to claim 11.
13. the capping agent contained in the raw material composition is a compound capable of becoming a monovalent ion, The method further includes a step of wet-mixing each of the raw materials of the raw material composition in a solvent containing water to obtain a raw material composition. The method for producing the black zirconia composite sintered body according to claim 11 or 12.
14. In the raw material composition, the stabilizer is ZrO 2 and HfO 2 The method for producing a black zirconia composite sintered body according to any one of claims 11 to 13, further comprising a stabilizer that is not solid-dissolved in the zirconia composite sintered body.
Citation Information
Patent Citations
Black-colored free-cutting ceramics, its manufacturing method and use thereof
JP2001354480A
Black zirconia sintered compact, raw material powder for the same, and method of manufacturing them
JP2006342036A
Machinable zirconia and method for producing the same
JP2015127294A
Black zirconia sintered body and use therefor
JP2017077976A